STUDY OF READING LEVELS AMONG STUDENTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This study was conducted to statistically assess the level of reading engagement among students, their reading habits, motivation, and the factors influencing these aspects. A total of 100 students participated in the research. The results revealed that students generally have a positive attitude toward reading; however, the level of regular reading remains moderate. Fiction was identified as the most frequently read type of literature. The findings emphasize the necessity of developing systematic pedagogical interventions to foster a culture of reading among students.